2016
DOI: 10.1159/000448717
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Adherence to Trifluridine and Tipiracil Hydrochloride for Metastatic Colorectal Cancer: A Retrospective Cohort Study

Abstract: Background: A novel oral agent that consists of trifluridine and tipiracil hydrochloride (TFTD) has been established as salvage-line treatment for metastatic colorectal cancer (mCRC). Adherence to TFTD is crucial to maintaining appropriate curative effects. This study sought to clarify adherence to TFTD and identify candidate factors deteriorating adherence at our institution. Methods: A total of 50 consecutive mCRC patients who received TFTD monotherapy between June 1, 2014 and July 31, 2015 were analyzed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Patients who were not treated in the Pharmaceutical Outpatient Clinic (POC) [9] or who were lost to follow-up were excluded. Patients who received preliminary treatment with steroids for any reason were also excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Patients who were not treated in the Pharmaceutical Outpatient Clinic (POC) [9] or who were lost to follow-up were excluded. Patients who received preliminary treatment with steroids for any reason were also excluded.…”
Section: Methodsmentioning
confidence: 99%
“…In that study, hand‐foot syndrome and liver dysfunction were much more common among patients treated with REG than those treated with FTD + TPI , and these two adverse events (AEs) are the most common causes of nonadherence to REG . Conversely, nausea and vomiting were more common among patients treated with FTD + TPI than those treated with REG, and these are among the most common factors associated with nonadherence to FTD + TPI . Therefore, these AEs appear likely to contribute to the difference in adherence observed in the current study, although this has not been formally evaluated.…”
Section: Discussionmentioning
confidence: 56%
“…To date, few studies have examined adherence to therapy in patients with mCRC using FTD + TPI or REG . A single‐center study using self‐reported treatment diaries to evaluate adherence in patients using FTD + TPI reported an adherence rate of 95.0%–98.2% .…”
Section: Discussionmentioning
confidence: 99%
“…One study showed a 95.0% to 98.2% adherence rate for FTD/TPI, which agrees with our reported mean MPR of 0.91. 20 In that study, Data presented as n (%) or mean AE standard deviation (median). Abbreviations: DOT ¼ duration of treatment; FTD/TPI ¼ trifluridine/tipiracil; MPR ¼ medication possession ratio; PDC ¼ proportion of days covered; REG ¼ regorafenib; TTD ¼ time to discontinuation.…”
Section: Discussionmentioning
confidence: 99%